Use of bibliometric modelling for policy making - Smith, Kerry; Marinova, D. (Elsevier, 2005)
Bibliometric methods for analysing and describing research output have been supported internationally by the establishment and operation of organisations such as the Institute for Scientific Information (ISI) as well as the continual calculations and release of journal lists, bibliometric indicators and rankings. Policy makers in Australia have been relying on such bibliometric information and analyses in making funding decisions and encouraging the development of research potential and strengths. Does bibliometric modelling of research productivity reflect the real impact research has for Australia's future? The paper is based on a study of three Australian research centres in the field of the geosciences. The analysis reveals a number of anomalies in the generalisations made when ISI models are used for policy decisions.